URGENSI MEMAHAMI KONSEP PERTUMBUHAN DAN PERKEMBANGAN YANG TERJADI PADA DIRI PESERTA DIDIK - Siregar, Tarmiji; Farhanah, Jihan; Nurbaithie, Siti; Masyitah, Siti (Cv Arsy Persada Quality, 2022)
Growth can be defined as an increase in size (physical) or a quantitative change. In the material as a result of environmental influences. This quantitative change can be an enlargement or increase from nothing, from small to large, from small to many and so on. While the term development is part of a qualitative process. Changes that refer to the quality of function of physical organs, not the physical organs themselves. In other words, the emphasis on the meaning of development lies in the improvement of psychological functions brought about by the physical organs. This theoretical analysis technique involves interpretation using a qualitative approach (critical reasoning). So the development of students, especially those who are in transition from childhood to adolescence and from adolescence to adulthood, affects many lines of life processes, including the learning process. From this it can be concluded, when students go through a period called the period of growth and development, they are very vulnerable to problems that will later affect their learning process at school. So before knowing how the problems are, the more important thing is to understand the concepts in the growth and development of students.